Dietary protein ingested before and during short photoperiods makes an impact on affect-related behaviours and plasma composition of amino acids in mice. Issue 10 (15th September 2015) - Otsuka, Tsuyoshi; Goda, Ryosei; Iwamoto, Ayaka; Kawai, Misato; Shibata, Satomi; Oka, Yoshiaki; Mizunoya, Wataru; Furuse, Mitsuhiro; Yasuo, Shinobu
Abstract: In mammals, short photoperiod is associated with high depression- and anxiety-like behaviours with low levels of the brain serotonin and its precursor tryptophan (Trp). Because the brain Trp levels are regulated by its ratio to large neutral amino acids (Trp:LNAA) in circulation, this study elucidated whether diets of various protein sources that contain different Trp:LNAA affect depression- and anxiety-like behaviours in C57BL/6J mice under short-day conditions (SD). In the control mice on a casein diet, time spent in the central area in the open field test (OFT) was lower in the mice under SD than in those under long-day conditions (LD), indicating that SD exposure induces anxiety-like behaviour. The SD-induced anxiety-like behaviour was countered by an α -lactalbumin diet given under SD. In the mice that were on a gluten diet before transition to SD, the time spent in the central area in the OFT under SD was higher than that in the SD control mice. Alternatively, mice that ingested soya protein before the transition to SD had lower immobility in the forced swim test, a depression-like behaviour, compared with the SD control. Analysis of Trp:LNAA revealed lower Trp:LNAA in the SD control compared with the LD control, which was counteracted by an α -lactalbumin diet under SD. Furthermore, mice on gluten or soya protein diets before transition to SD exhibited high Trp:LNAA levels in plasma under SD. In conclusion, ingestion of specific proteins at different times relative to photoperiodic transition may modulate anxiety- and/or depression-like behaviours, partially through changes in plasma Trp:LNAA.